Translation and Cross-Cultural Adaptation of the Instrument for the Diagnosis of the Complexity of Palliative Care Needs - Filippo Canzani; Sara Alquati; Francesca Bordin; Christian Barillaro; Marta De Angelis; Grazia Di Silvestre; Sabrina Dispenza; Gino Gobber; Caterina Magnani; Pietro Manno; Fiammetta Cosci; Silvia Tanzi (Palliative Medicine Reports)
Background: In recent years, the palliative care (PC) paradigm is evolving from a prognosis-based approach to one centered on complexity, also in response to the aging population and the increase in chronic diseases. It is therefore necessary to strengthen PC networks with effective management of the specialist resources available. The use of tools such as the spanish Diagnostic Instrument for Complexity in Palliative Care (IDC-Pal) can help evaluate the complexity of PC needs, thus guiding the clinical care response. The aims of this study were the translation and the cultural adaptation of the IDC-Pal tool to the Italian language. Methods: The methodology proposed by Beaton et al. and Sousa et al. was used for the translation and cultural adaptation of the IDC-Pal tool. Phase 1: a forward–backward translation with linguistic and cultural adaptation of the tool by two native Spanish translators and two native Italian translators, including two PC professionals and two nonprofessionals, was performed. Phase 2: the translation was evaluated by a panel of 12 Italian PC experts, who assessed the comprehensibility of the translated instrument, and proposed changes to the text, which was found to be incomprehensible to at least 20% of them. Phase 3: this version of the tool was proposed to a sample of the Italian target population (93 professionals including general practitioners, nurses, and hospital doctors at 9 Italian PC networks tested it on 168 patients in home and hospital settings), to evaluate its comprehensibility and usability. At the end of the experimental phase, a semi-structured interview was organized with the main researcher of each network, with the aim of receiving information about the comprehensibility of the tool. Finally, a definitive version was developed. Results: The translation and adaptation were achieved without major problems. Conclusions: A conceptually, culturally, and linguistically equivalent italian version of the original IDC-Pal was obtained.